CoSe-catalyzed growth of graphene sheath to construct CNF@graphene-CoSe cable/sheath heterostructure for high-performance Lithium–Sulfur batteries. (February 2023) - Cao, Zhaoxia; Wang, Yahan; Guo, Jian; Jia, Jingyi; Zhang, Zhennan; Cui, Yuantao; Yin, Yanhong; Yang, Mingguo; Yang, Shuting
Abstract: Advanced hierarchical hybrid nanostructures of polar, conductive and catalytic chemical traps/carbon with rationally tailored components, structures, and chemistries are important in determining the performance of lithium-sulfur (Li–S) batteries. Herein we propose a facile strategy to prepare 3D-structured CNF@graphene-CoSe (CNF@GL -CoSe) cable/sheath heterostructure with the in-situ formed CoSe as a catalyst for graphene-like carbon growth and Se as a catalyst promoter. The architecture integrates high electrical conductivity, effective ion transport, notable polysulfide entrapment, and polysulfide redox kinetics, availing lithium/sulfur conversion when applied as an interlayer in a Li–S battery. As expected, the battery delivered a low decay of 0.053% per cycle over 700 cycles at 1 C. The capacity even remained 649.4 and 524.5 mA h g −1 at 4 and 6 C, respectively. Furthermore, an areal capacity of about 3 mA h cm −2 at 0.1 C after long-term tests can still maintain with sulfur loading of 4.5 mg cm −2 . Graphical abstract: A facile effective strategy to prepare 3D-structured CNF@graphene-CoSe cable/sheath heterostructure with the in situ formed CoSe as a catalyst for graphene-like carbon growth and Se as a catalyst promoter, achieving significant enhancement in electrochemical performance of Li–S batteries. Image 1 Highlights: In situ constructing CNF@graphene-CoSe cable/sheath heterostructure. CoSe catalyzes the growth of graphene sheath and Se as a catalyst promoter. Synergism of conductivity, absorption and catalysis. Enabling excellent performance as an interlayer.